Oxidative cyanation of N-aryltetrahydroisoquinoline induced by visible light for the synthesis of α-aminonitrile using potassium thiocyanate as a "CN" agent. Issue 51 (19th September 2019) - Yi, Bing; Yan, Ning; Yi, Niannian; Xie, Yanjun; Wen, Xiaoyong; Au, Chak-Tong; Lan, Donghui
Abstract : A novel method for the synthesis of α-aminonitrile, through visible-light-induced oxidative cyanation of N -aryltetrahydroisoquinoline with potassium thiocyanate, has been developed. Abstract : A novel method for the synthesis of α-aminonitrile through visible-light-induced oxidative cyanation of N -aryltetrahydroisoquinoline with potassium thiocyanate has been developed. The process does not require the use of a photocatalyst, transition metal reagent, strong oxidizing agent, or toxic cyano-containing compound, which makes the reaction simple and green.